Pemesanan E-Tiket Speed Boat Online Berbasis Website Studi Kasus PT.Caspla Bali Seaview - Dewa Gede Komala Putra; I Gede Putu Krisna Juliharta; I Gusti Lanang Agung Raditya (Primakara University, 2019)
Information needs with the rapid advancement of information technology, ease of accessing information is absolutely necessary so that users or users are more practical in obtaining information, information and information management in an integrated manner are very important in every institution, including in seeking information on purchasing services. Demands for ease of accessing rental service information are increasing, such as the ease of finding information on ticket purchasing services, from destination to destination, price, departure time. And in this case looking for information on purchasing speed boat tickets, we still use manual methods such as browsing to the web boat address that will be used to cross, but here we are still confused about the web information. The purpose of this research is to find out the departure schedule information, make it easier to find information and clarify the effectiveness of the speed boat booking system. Based on the constraints above, the author plans to design a website-based application system that can clearly provide information from the contents of the company profile and make direct booking transactions through the website without coming directly to the ticket sales location. Results of research and discussion and constraints that has been stated, the following are some suggestions that are expected to be input to researchers as material for consideration in providing motivation for further research. In designing the website for the future, fill in the payment gateway to make it easier in the process of further payments and also to strengthen it with an online server so that it updates the deadline for confirmation of payment for E-ticket orders that have not been paid off.